2013
DOI: 10.1017/s1463423612000655
|View full text |Cite
|
Sign up to set email alerts
|

The health promotion work of the district nurse: interpreting its embeddedness

Abstract: Embeddedness is a significant issue for learning in practice. The ability of experienced community nurses to interpret and articulate the concept of health promotion clearly and to make tacit knowledge evident would be of benefit to students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…The idea that NPs need ability to create a confidential nursing relationship with patients reached a consensus level of 91·1% in this study. This finding has been reported in previous studies as competence with respect to attitudes, including factors such as advocacy or encouraging the patient to participate in decision‐making (Irvine , Runciman ). In this study, the level of consensus as to whether NPs need to have knowledge of how to prevent diseases reached 89·3%.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…The idea that NPs need ability to create a confidential nursing relationship with patients reached a consensus level of 91·1% in this study. This finding has been reported in previous studies as competence with respect to attitudes, including factors such as advocacy or encouraging the patient to participate in decision‐making (Irvine , Runciman ). In this study, the level of consensus as to whether NPs need to have knowledge of how to prevent diseases reached 89·3%.…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, studies have found that individual and holistic perspectives, including helping people make health decisions and become engaged in changing unhealthy lifestyles, are the main health promotion activities in nursing (Povlsen & Borup , Speller et al . , Runciman ). Case management competence in health promotion indicated a need to have knowledge of common public health problems, and a level of consensus (94·6%) was reached in this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations